Ecological and sociological spectrum of Ostericum palustre at new localities in central Poland - Michalska-Hejduk, Dorota; Kopeć, Dominik (Biodiversity: Research and Conservation, 2011)
The paper presents new data on the distribution of Ostericum palustre (a strictly protected vulnerable species) in central Poland. In the period of 2008-2009, new population of this species were found in the north-eastern part of Łódź Province. Ostericum palustre was present in the described localities in meadow, herb, peat bog and reed bed communities. The species was most numerous in well preserved purple moor-grass meadows. New localities of Ostericum palustre described in the article are instrumental in the protection of this species in central Poland.